An assembled molecular signaling map of interleukin-24: a resource to decipher its multifunctional immunoregulatory role in pathophysiological conditions - Aravind, Anjana; Shaji, Vineetha; Ahmed, Mukhtar; Dagamajalu, Shobha; Vijayakumar, Manavalan; Prasad, Thottethodi Subrahmanya Keshava; Raju, Rajesh (Frontiers in Immunology, 2025)
IntroductionInterleukin-24 (IL-24) is a cytokine belonging to the IL-10 family with immunoregulatory properties. It is known to induce cellular responses in various disease conditions, including inflammatory, infectious diseases, and cancer, in a receptor-dependent and independent manner. IL-24 is induced by both immune and non-immune cells and acts on a vast array of target cells to regulate various biological processes. The antitumor and immunoregulatory properties of IL-24 support its application as a therapeutic agent in a vast array of pathological conditions. Characterizing the molecular events associated with its immunomodulatory properties is essential for evaluating its utility in cancer immunotherapy.MethodsThe data related to signaling events induced by IL-24 were then manually annotated and cataloged from the literature pertaining to IL-24 signaling. The cataloged molecular events were then manually drawn based on the topology as a signaling pathway map of IL-24.ResultsBased on the data mined from published literature, we assembled IL-24-regulated signaling events linked to its immunoregulatory and anti-tumor activities. The receptor-ligand interaction of IL-24 regulates multiple downstream signaling cascades, leading to antitumor activities alongside inducing inflammatory reactions and anti-infectious processes. We provide a signaling pathway map of IL-24 consisting of 433 mRNAs/proteins and their 613 signaling events.DiscussionWe believe this map would serve as a knowledge base for reference and one-go visualization of the signaling events identified to be induced by IL-24. Moreover, this map is made available (https://ciods.in/il24/) for the researchers to explore the role of IL-24 in various pathophysiological conditions through the gene set enrichment of transcriptomics or proteomics datasets from various disease conditions.